BARRIERS TO INITIATION AND COMPLETION OF THE 2-DOSE HPV VACCINE AMONG GIRLS AGED (9-16) YEARS IN BARAPWO WARD, LIRA CITY IN NORTHERN UGANDA, A CROSS-SECTIONAL STUDY - Sseguya , Mathias; Omute, Tom (SJ Insights, 2025)
Background Cervical cancer is the principal burden of Human Papillomavirus (HPV) infections and a public health priority. Since 2008, HPV vaccination has been routinely recommended for pre-adolescents and adolescent girls in Uganda as the primary preventive measure for cervical cancer. Therefore, the study aims to identify the barriers to initiating and completing the 2-dose HPV vaccine among girls aged (9-16) years in Barapwo ward, Lira City in northern Uganda. Methods An analytical cross-sectional study was conducted among 245 primary school girls aged 9-16 in Barapwo ward, Lira City West Division. A multistage sampling technique was used to select eligible participants, and data was collected using an interviewer-administered questionnaire. The data was analyzed using SPSS version 20, and descriptive statistics were used. Results The study group comprised participants aged 9 to 16 years, with a mean age of 12.84. Most participants (33.9%) were in primary six, and the majority (90.2%) were from the Lango tribe. Among the girls, 41.2% identified as Protestants and Catholics, while 73.1% lived in nuclear families and 26.9% in extended families. Factors that were found significantly associated were; having heard about the vaccine, P<0.001], knowledge of where to find the vaccine[OR=(95% CI:0.131-0.438), P<0.001], radio access, P<0.001], being taught about cervical cancer and HPV at school, P<0.001], in-school vaccination[OR=(95%CI:6.621-30.825), P<0.001], distance to the health facility[OR=(95% CI:0.132-0.41), P<0.001], health workers recommendation and exposure to clinical outreaches. Conclusion The study identified critical factors influencing HPV vaccination uptake, including awareness, education, and accessibility. Recommendations Health policymakers should create multilingual awareness strategies to boost HPV vaccine uptake in Lira City. Future research is needed to examine factors influencing vaccine uptake and effective interventions. The Ministry of Health and religious leaders should educate communities and health workers to promote vaccination.